EFEKTIVITAS PENERAPAN SISTEM ABSENSI GURU BERBASIS GEOLOKASI MENGGUNAKAN METODE FEATURE DRIVEN DEVELOPMENT (FDD) DI SMP NEGERI 2 RIAU SILIP - deswita, deswita; Irwan; Wathan, M Hizbul (KHARISMA Tech, 2025)
The supervision of teacher attendance plays a crucial role in ensuring the smooth implementation of the learning process. However, the manual attendance system used at SMP Negeri 2 Riau Silip often leads to recording errors, time inefficiency, and data manipulation. This study aims to implement and evaluate the effectiveness of a teacher attendance system based on geolocation using the Feature Driven Development (FDD) method. The system was developed with the Flutter framework for the mobile application and Laravel for the backend, integrated through an API and supported by a MySQL database. The main features include GPS-based attendance validation, photo-based activity verification, attendance history, and real-time monitoring by administrators. The development process followed five stages of FDD, ensuring a structured and feature-oriented approach. System testing using black box testing and User Acceptance Testing (UAT) resulted in an average feasibility score of 89.73%, categorized as highly feasible. The results indicate that the implementation of the geolocation-based attendance system effectively improves efficiency, accuracy, and transparency in managing teacher attendance at SMP Negeri 2 Riau Silip.